(untitled) (Global Journal of Management and Business Research, 2020)
Our work aims to study management control practices (MCP) in small agribusinesses (SA) in the Beni Mellal-Khénifra region. Semi-structured interviews, observations and document analysis were used to collect the data. The owners and executives of the production units surveyed were interviewed. The findings of the study show that the management control practices of these companies are strongly affected by the traditional cultural norms of Moroccan society. Predominant management control practices include "power sharing among family members", Paternal governance, verbal communication, clan selection of employees, friendly and horizontal relationships. These practices have often favored centralized decision-making processes in all aspects of the operations of these companies. These results call for new research of the same nature to explain the relationship between these practices and the financial performance of these companies.